'Unusual ingredients': Developing a cross-domain model for multisensory artistic practice linking food and music. (1st October 2021) - Thompson-Bell, Jacob; Martin, Adam; Hobkinson, Caroline
This article explores linkages between sensory experiences of food and music in light of recent research from gastrophysics, 4E cognition (i.e. embodied, embedded, extended and enactive) and ecological perception theory. Drawing on these research disciplines, this article outlines a model for multisensory artistic practice, and a taxonomy of cross-domain creative strategies, based on the identification of sensory affordances between the domains of food and music. Food objects are shown to 'afford' cross-domain interrelationships with sound stimuli based on our capacity to sense their material characteristics, and to make sense of them through prior experience and contextual association. We propose that multisensory artistic works can themselves afford extended forms of sensory awareness by synthesizing and mediating stimuli across the selected domains, in order to form novel, or unexpected sensory linkages. These ideas are explored with reference to an ongoing artistic research project entitled 'Unusual ingredients', creating new music to complement and enhance the characteristics of selected food.